Expeditionary anthropology teamwork, travel and the 'science of man' - Thomas, Martin 1964-; Harris, Amanda 1976- (New York Berghahn, 2018)
The origins of anthropology lie in expeditionary journeys. But since the rise of immersive fieldwork, usually by a sole investigator, the older tradition of team-based social research has been largely eclipsed. Expeditionary Anthropology argues that expeditions have much to tell us about anthropologists and the people they studied. The book charts the diversity of anthropological expeditions and analyses the often passionate arguments they provoked. Drawing on recent developments in gender studies, indigenous studies and the history of science, the book argues that even today, the 'science of man' is deeply inscribed by its connections with expeditionary travel.
Anthropology and the expeditionary imaginary : an introduction to the volume / Martin Thomas and Amanda Harris -- Assembling the ethnographic field : the 1901-02 expedition of Baldwin Spencer and Francis Gillen / Philip Batty -- Receiving guests : the Cambridge Anthropological Expedition to Torres Straits 1898 / Jude Philp -- Donald Thomson's hybrid expeditions : anthropology, biology and narrative in northern Australia and England / Saskia Beudel -- Looking at culture through an artist's eyes : William Henry Holmes and the exploration of Native American archaeology / Pamela M. Henson -- The anomalous blonds of the Maghreb : Carleton Coon invents the African Nordics / Warwick Anderson -- Medium, genre, indigenous presence : Spanish expeditionary encounters in the Mar del Sur, 1606 / Bronwen Douglas -- Ethnographic inquiry on Phillip Parker King's hydrographic survey / Tiffany Shellam -- Gender and the expedition : feminist anthropologist Elsie Clews Parsons and the politics of fieldwork in the Americas in the 1920s and 1930s / Desley Deacon -- What has been forgotten? The discourses of Margaret Mead and the American Museum of Natural History Sepik expedition / Diane Losche -- Gender, science and imperial drive : Margaret McArthur on two expeditions in the 1940s / Amanda Harris.
Includes bibliographical references and index.
Keywords: Anthropology -- Fieldwork; Anthropology -- Research; Scientific expeditions